Comparative evaluation of serum superoxide dismutase and glutathione levels in periodontally diseased patients: An interventional study - Thomas Biju; M Madani Shabeer; Ramesh Amitha; B Prasad Rajendra; Kumari Suchetha (Wolters Kluwer Medknow Publications, 2014)
Background: Periodontal disease is an immune-inflammatory disease characterized by connective tissue breakdown, loss of attachment, and alveolar bone resorption. Under normal physiological conditions, a dynamic equilibrium is maintained between the reactive oxygen species (ROS) and antioxidant defense capacity. Oxidative stress occurs when this equilibrium shifts in favor of ROS. Oxidative stress is thought to play a causative role in the pathogenesis of periodontal diseases. Aim: The present study was designed to estimate and compare the superoxide dismutase (SOD) and glutathione (GSH) levels in the serum of periodontitis, gingivitis, and healthy individuals before and after nonsurgical periodontal therapy. Materials and Methods: The present study was conducted in the Department of Periodontics, A. B. Shetty Memorial Institute of Dental Sciences, Deralakatte, Mangalore. The study was designed as a single blinded interventional study comprising 75 subjects, inclusive of both sexes and divided into three groups of 25 patients each. Patients were categorized into chronic periodontitis, gingivitis, and healthy. The severity of inflammation was assessed using gingival index and pocket probing depth. Biochemical analysis was done to estimate the SOD and GSH levels before and after nonsurgical periodontal therapy. Results obtained were then statistically analyzed using ANOVA test and paired t-test. Results: The results showed a higher level of serum SOD and GSH in the healthy group compared to the other groups. The difference was found to be statistically significant (P < 0.0001). The post-treatment levels of SOD were statistically higher than the pre-treatment levels in periodontitis and gingivitis group.